2009
DOI: 10.1258/phleb.2009.008081
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy of varicose veins in patients with documented thrombophilia: a prospective controlled randomized study of 105 cases

Abstract: Objectives The aim of this study was to assess thrombotic complications following sclerotherapy in thrombophilic patients in combination with thromboprophylaxis, in two randomized arms using low molecular weight heparin (LMWH) or warfarin. Patients and methods This study received approval from the Ethics Committee. A total of 105 patients (81 females, 24 males) ranging in age from 20 to 82 years (mean 50) were selected: 75 with Factor V Leiden mutation, 18 with prothrombin 20210A mutation, 7 with high level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
(12 reference statements)
1
17
0
3
Order By: Relevance
“…28 Today, USGFS is widely accepted as a treatment of primary venous incompetence (long and short saphenous), 4 isolated incompetent saphenous tributaries, 29 reticular VV, 4 recurrent VV after surgery, 10 patients with venous leg ulcers, 30 and on patients with thrombophilia, provided they received anticoagulants. 31 Doctors should be aware of the advantages and limitations of different sclerosants, different concentrations of the same sclerosant, and the different techniques for injection. 16 A randomized clinical trial of the duration of compression therapy (1 vs 3 weeks) after uncomplicated high SFL with stripping of the GSV found no benefit in patients wearing graduated elastic compression stockings for Ͼ1 week with respect to postoperative pain, number of complications, time to return to work, or patient satisfaction for up to 12 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…28 Today, USGFS is widely accepted as a treatment of primary venous incompetence (long and short saphenous), 4 isolated incompetent saphenous tributaries, 29 reticular VV, 4 recurrent VV after surgery, 10 patients with venous leg ulcers, 30 and on patients with thrombophilia, provided they received anticoagulants. 31 Doctors should be aware of the advantages and limitations of different sclerosants, different concentrations of the same sclerosant, and the different techniques for injection. 16 A randomized clinical trial of the duration of compression therapy (1 vs 3 weeks) after uncomplicated high SFL with stripping of the GSV found no benefit in patients wearing graduated elastic compression stockings for Ͼ1 week with respect to postoperative pain, number of complications, time to return to work, or patient satisfaction for up to 12 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The VTE complication rate compares well with that reported after surgery, RFA, and EVLT; especially bearing in mind of the numbers of older C5/C6 patients. [25][26][27][28] All symptomatic DVT/PE occurred within 1 month. No asymptomatic DVTs were observed.…”
Section: Patientmentioning
confidence: 99%
“…23 There are no randomized placebo-controlled trials concerned with the efficacy of pharmacological thromboprophylaxis in ambulatory endovenous surgery to guide us. The only indication that it might be effective in patients with increased risk comes from a publication of Hamel-Desnos et al 24 In an earlier retrospective study they had found 5 cases of DVT in 56 patients (9%) with thrombophilia treated with sclerotherapy. In a prospective study, 105 patients with established thrombophilia scheduled for sclerotherapy (mostly UGSF of saphenous veins and tributaries) were randomized to single shot prophylaxis with nadroparine (4000 IU) immediately before treatment or to fixed low dose (1 mg) of warfarin starting 10 days before first treatment session and continued until 4 weeks after the last treatment session.…”
Section: Discussionmentioning
confidence: 99%